Glyoxalase 1 gene expression in various types of cancer cells immunopathology: a pan-cancer analysis study - Alaseem, Ali M.; Aldali, Jehad A.; Alasiri, Glowi; Alhujaily, Muhanad; AlHussaini, Khalid I.; AlKhamees, Osama A. (Frontiers in Oncology, 2025)
Metabolic reprogramming within the tumor microenvironment significantly affects cancer progression by shifting toward aerobic glycolysis and lactate production, while also supporting mitochondrial oxidative phosphorylation. The glyoxalase system, comprising GLO-1 and GLO-2, maintains metabolic homeostasis by neutralizing methylglyoxal (MG) byproducts. GLO-1 protects cells from damage by detoxifying MG via glutathione. In the curent study, pan-cancer analysis revealed elevated GLO-1 mRNA levels across various malignancies, exhibiting variable prognostic implications on patient survival: reduced survival in ACC, MESO, and SARC, and enhanced survival in KIRC and LIHC. GLO-1 activity is regulated by transcriptional and post-translational modifications, including phosphorylation, NO-mediated modification, and glutathionylation. The role of GLO-1 in survival and disease course differs depending on the specific cancer. GLO-1 levels were associated with immunotherapy markers like microsatellite instability (MSI) and tumor mutational burden (TMB), with positive correlations between GLO-1 and MSI in UCEC, TGCT, and STAD, and between GLO-1 and TMB in LUAD, UCEC, LIHC, MESO, SKCM, and READ. In terms of immune cell presence, GLO-1 was associated with increased endothelial and neutrophil cells, decreased T and B cell populations, and increased activated CD4 T cells, memory B cells, and type 2 helper T cells. In summary, our study highlights GLO-1 as a significant biomarker across multiple cancers that plays a key role in cancer progression, immune modulation, and therapeutic response.